2016
DOI: 10.1007/s00228-016-2018-0
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of vancomycin in patients with severe acute pancreatitis

Abstract: The serum trough concentration of vancomycin was significantly reduced in SAP patients. Higher dosage regimens are needed to ensure the clinical effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Vancomycin Ctroughs were significantly reduced in this subpopulation and, therefore, patients with severe acute pancreatitis need higher doses to ensure clinical effects …”
Section: Therapeutic Drug Monitoringmentioning
confidence: 97%
See 1 more Smart Citation
“…Vancomycin Ctroughs were significantly reduced in this subpopulation and, therefore, patients with severe acute pancreatitis need higher doses to ensure clinical effects …”
Section: Therapeutic Drug Monitoringmentioning
confidence: 97%
“… Severe acute pancreatitisVancomycin Ctroughs were significantly reduced in this subpopulation and, therefore, patients with severe acute pancreatitis need higher doses to ensure clinical effects Trauma patientsVancomycin pharmacokinetics in this subpopulation is best described by a two‐compartment open model; Clcr was related to Clvan (0.49 L/h) and decreases in the presence of furosemide (0.34 L/h).…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Recently, augmented renal clearance (ARC) has been proposed to describe the enhancement of renal elimination of circulating solutes observed in critically ill patients [19]. Most studies have shown that hyperdynamic circulation is characterized by increased renal blood flow with an increase in glomerular filtration rate as a potential mechanism [20]. Nevertheless, no information was given concerning the number of oncological patients in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The vancomycin dosage was administered over a 1-hour period. The steady state vancomycin trough concentration was measured prior to subsequent treatment to adjust dose and dose intervals [8] . The target serum vancomycin trough concentrations ranged from 10-15 or 15-20 mg/L [9].Serum vancomycin concentrations were measured by FPIA method using a Cobas 6000 c501 analyzer (Roche Diagnostics, China).…”
Section: Pharmacokinetic Analysis and Vancomycin Therapeutic Drug Monmentioning
confidence: 99%
“…Vancomycin serum trough concentrations are correlated with a variety of factors, including renal function, which is one of the most commonly recognized 9,10 . Age, 9,11 blood level of albumin, 11 sepsis duration, 10 and the time from severe acute pancreatitis onset to vancomycin therapy 11 have also been identified as variables that influence vancomycin concentrations. However, the results of different studies are not consistent.…”
Section: What Is Known and Objectivementioning
confidence: 99%